Improving English Pronunciation Skills through AI-Based Speech Recognition Technology - Dja'far, Veri Hardinansyah; Hamidah, Fitria Nur (Ethical Lingua: Journal of Language Teaching and Literature, 2024)
This research examines the effectiveness of AI-based speech recognition technology in fostering English pronunciation skills among students. The study emphasizes the importance of pronunciation proficiency as a cornerstone of language learning and its impact on overall communication effectiveness. A quasi-experimental design with a pretest-posttest control group methodology was employed. The participants were 58 third-year Accounting Diploma students from State Polytechnic of Malang, Indonesia. They were divided into two groups: an experimental class utilizing the Google Read Along application and a control class receiving conventional teaching methods. The results demonstrate a significant improvement in pronunciation skills within the experimental group. These students achieved an average N-Gain score of 0.7646, categorized as "high," compared to the control group's average score of 0.6564, classified as "moderate." Furthermore, a t-test analysis revealed a statistically significant difference between the two groups, with a p-value (2-tailed) of 0.000. These findings strongly suggest that AI-based speech recognition technology offers a more effective approach to enhancing English pronunciation compared to conventional methods. This research paves the way for integrating this technology into language learning curriculums. The potential for significant positive impacts on student pronunciation skills is promising and warrants further exploration in future research endeavors.